Public and Private Sector Differences: CEOs' Perceptions of Their Role Environments - Lachman, Ran (Academy of Management Journal, 1985)
Comparative studies of private and public sector organizations often consider organizations with dissimilar tasks or business purposes: profit-making business firms commonly represent the private sector, and nonprofit service or government regulatory agencies commonly represent the public sector. However, these studies generally have not accounted for this difference in business purpose, and have attributed the differences that have frequently been observed to organizations' affiliations with the presumably different sectors (e.g., Blumenthal, 1979; Buchanan, 1975; Guyot, 1962; Rainey, 1983; Rainey, Backoff, Wamsley & Zald, 1976). The argument for this all too common use of the distinction between public and private sectors as the basis of a framework for interpreting observed differences is that the legitimizing goals and basic orientations of the two sectors vary, and so determine different institutional milieux for organizations affiliated with each. Hence, investigators expect differences between the two sectors in organization-environment relations and in managerial practices. The purpose of this study is to examine whether or not these commonly expected private-public differences emerge from a comparison of environmental perceptions of chief executive officers (CEOs) of organizations having similar task environments?that is, public and private industrial organizations. If, when similar organizations are compared, the expected differences in perceived environments appear, the case for sector differences would be considerably strengthened. But, if such a comparison fails to support the expected differences, it will suggest that perceived differences in organization-environment relations are probably due to differences in task or functional environments, rather than to sector affiliation.